Hurricane Katrina: measuring disaster impacts - Sanders, Mark; Schippers, Vincent (Henry Stewart Talks, 2022)
This case study examines light emissions as an indicator of economic activity in areas affected by Hurricane Katrina in 2004-5, thereby addressing the challenge in measuring local economic impacts of natural disasters.